Who Rules the World? A Portrait of the Global Leadership Class. Issue 4 (December 2019) - Gerring, John; Oncel, Erzen; Morrison, Kevin; Pemstein, Daniel
Abstract : It goes without saying that "leaders rule." And it stands to reason that the background characteristics of leaders affect the way they rule. Who are the leaders of the world? We generate a composite portrait of the global political elite with data from the Global Leadership Project (GLP), the first dataset offering biographical information on a wide array of leaders in most countries of the world. We offer comparisons across office, regions, regime types, and level of development. And we enlist the variables in the dataset in a latent class model to arrive at an empirical typology of political leaders around the world.